2013
DOI: 10.1002/anie.201209159
|View full text |Cite
|
Sign up to set email alerts
|

Epoxide‐Opening Cascades Triggered by a Nicholas Reaction: Total Synthesis of Teurilene

Abstract: Natural inspiration: Based on the biosynthesis of squalene‐derived polyethers, a total synthesis of teurilene is described. The carbocation formation in the Nicholas reaction serves to control the initiation of a polyepoxide ring‐opening cascade. The three furan rings present in teurilene were obtained in excellent yield in one step. Boc=tert‐butoxycarbonyl, TMS=trimethylsilyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 43 publications
1
15
0
2
Order By: Relevance
“…27 Toward this end, several acids were tested: BF 3 .Et 2 O resulted in the degradation of the starting compound and gentle Montmorillonite K-10 acid remained inefficient. Finally, the authors observed the desired cyclized product after purification on silica and could therefore carry out the cyclization step using SiO 2 in dichloromethane, followed by deprotection using CAN, which allowed them to complete the synthesis of Teurilene.…”
Section: Scheme 6 : Amberlyst-15 Promoted Cyclization For the Synthesmentioning
confidence: 99%
“…27 Toward this end, several acids were tested: BF 3 .Et 2 O resulted in the degradation of the starting compound and gentle Montmorillonite K-10 acid remained inefficient. Finally, the authors observed the desired cyclized product after purification on silica and could therefore carry out the cyclization step using SiO 2 in dichloromethane, followed by deprotection using CAN, which allowed them to complete the synthesis of Teurilene.…”
Section: Scheme 6 : Amberlyst-15 Promoted Cyclization For the Synthesmentioning
confidence: 99%
“…Professor Wiemer has cleverly employed a Lewis acid-catalyzed oxirane cascade involving a phenol en route to schweinfurthin G, while Professor Martin has established that teurilene can be assembled via a triflic acid-catalyzed cascade (Scheme 14) [21,22]. Both cascades proceed in good yields.…”
Section: Oxiranes In Ring-expansion Cascadesmentioning
confidence: 99%
“…In Figure 2 are the structures of the natural products for which the highlighted strategic bonds were formed via a Nicholas reaction. Name-ly, deformylflustrabromine (100), 200 (-)-allocolchicine (101), 201 velloziolide (102), 202 teurilene (103), 203 (±)-microstegiol (104), 204,205 (-)-isolaure-pinnacin (105) and (+)rogoioloxepane A (106), 206 (+)-cis/(-)-trans-lauthisan (107) and (+)-cis/(-)-trans-obtusan (108), 207 (+)-laurencin (109), 208 as well as formal synthesis and approaches towards the frameworks of icetexane and faveline ring-systems, 209 the framework of solanoeclepin A, 210 and natural product related benzopyran 211 and dibenzocyclooctynes 212 have been described.…”
Section: Scheme 60mentioning
confidence: 99%